CASE-BASED REASONING (CBR) DAN PENGARUHNYA TERHADAP PENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH - Deni Darmawan; Ayu Puji Rahayu (Kwangsan: Jurnal Teknologi Pendidikan, 2016)
This study focuses on efforts to solve the problems of the low ability students in solving difficulties in learning Indonesian language as a subject matter. The objective of this research is directed at efforts of explaining the influence of Case based Reasoning (CBR) in the learning towards the students’ problem-solving abilities. The method is a quasi-experimental research focusing on students of MA (Madrasah Aliyah or Islamic Senior High School) in one of the districts in West Java, where the learning in the control class using the Problem Based Learning (PBL). The research showed that the students’ problem-solving abilities by using CBR model is 44% in the high interpretation and by 56% in the moderate interpretation. Whereas the learning using the PBL model is 28% in the high interpretation, 56% in the medium interpretation, and 16% in the low interpretation. The value obtained through testing the hypothesis is z-score = -3089 smaller than z-table = -1.64. It means that Ho is refused and Ha is accepted. It further means that there is a significant difference between the problem-solving ability of students of using CBR model in learning and the students using PBL model in learning. The conclusion of this study indicates that the use of CBR model (designed for the study) has proved to give an effect to the problem-solving skills of students learning Indonesian subject. AbstrakPenelitian ini memfokuskan pada upaya pemecahan permasalahan mengenai rendahnya kemampuan siswa dalam memecahkan kesulitan-kesulitan ketika mempelajari materi pelajaran Bahasa Indonesia. Tujuan penelitian ini diarahkan pada upaya menjelaskan pengaruh Case-Based Reasoning (CBR) dalam pembelajaran terhadap kemampuan pemecahan masalah siswa. Metode penelitian adalah kuasi eksperimen dengan objek penelitian adalah siswa MA di salah satu kabupaten di Jawa Barat, di mana pembelajaran yang digunakan oleh kelas kontrol adalah Pembelajaran Berbasis Masalah (PBL). Hasil penelitian menunjukkan bahwa kemampuan pemecahan masalah siswa dengan menggunakan model pembelajaran CBR sebesar 44% dalam interpretasi tinggi dan sebesar 56% dalam interpretasi sedang. Sedangkan pembelajaran menggunakan model pembelajaran PBL sebesar 28% dalam interpretasi tinggi, sebesar 56% dalam interpretasi sedang dan 16% dalam interpretasi rendah. Sementara berdasarkan hasil uji hipotesis diperoleh nilai zhitung = -3.089 lebih kecil dari ztabel = -1.64. Hasil pengujian ini menunjukan bahwa Ho ditolak atau Ha diterima, artinya ada perbedaan secara signifikan antara kemampuan pemecahan masalah siswa yang menggunakan model pembelajaran CBR dan siswa yang menggunakan model pembelajaran PBL. Simpulan penelitian ini menunjukkan bahwa penggunaan CBR yang dirancang selama penelitian ternyata terbukti memberikan pengaruh terhadap kemampuan pemecahan masalah oleh siswa